A fault alarm monitor method for safety-critical software. Issue 1 (August 2021) - Yu, Yi; Wang, Xiaoyong; Shi, Cong; Chu, Pengzi; Xu, Ye
Abstract: A design by contract (DBC) technology-based software fault alarm monitor method is discussed in this paper. Firstly, this method assigns a static module code to each software module, and assigns a static fault code to each fault alarm message in the software module. When the software is running, the dynamic module code is allocated before the software module is executed. When the software module is executed, the current module code is record, the fault alarm message is checked and collected. When a fault information is detected, all internal states of the system are recorded to the external memory, and the system is oriented to safety. At the end of the normal execution of the software module, the recorded current module code is erased. Finally, the fault analysis diagnostic tool is used to analyse the output fault message. Compared with the previous methods, the method can quickly locate the fault location, analyse the cause of the alarm, and improve the safety and maintainability of the software.